The Meaningfulness of Life in Multiethnic Perspective as the Foundation for Personal Guidance - Batubara, Juliana (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2018)
This study aims to describe the meaningfulness of life in a multi-ethnic perspective in the Guidance and Counseling (BK) program, Postgraduate School of Universitas Pendidikan Indonesia (UPI). The scope of this study is the understanding of self, the meaning of life, changing attitudes, self-attachment, directed activities and social support. Data about the meaningfulness of life is obtained by using a questionnaire instrument that has been prepared by the author and disseminated to postgraduate students of BK UPI. The results of this study aims to recognize the student's self potential, so it can be directed to a more positive and become the foundation in personal guidance.